KAJIAN TEOLOGIS DAMPAK COVID 19 TERHADAP PERILAKU ANAK DI KELUARGA KRISTIANI - Theodora Desy Natalia; Singgih Prastawa (CV. ADIBA AISHA AMIRA, 2023)
This pandemic has resulted in children attending school online, leading to a lack of socialization among them. The impact on children has caused them to exhibit negative behavior, including a loss of respect, particularly towards elders. The role of parents is crucial in addressing this issue, as they serve as role models for their children. Therefore, parents need to be firm and teach values to their children. The objective of this article is to examine or explain the roles of parents in shaping the Christian character of children, aligning their character with what God desires. This study employs a qualitative method with a phenomenological approach. The research subjects are congregants of a Pentecostal Christian Church. The study explores events occurring within the church and its environment. Data collection instruments include interviews, observations, and document analysis. The data analysis follows Miles and Huberman's interactive analysis, involving data collection, data reduction, data presentation, and drawing conclusions. To ensure data validity, triangulation of sources and techniques were employed to strengthen the results. The observed behavior during the pandemic includes a lack of consistency in engaging in worship activities. Based on these findings, there is a need for a theological approach that instills the fear of God, encouraging congregants to behave respectfully in church and society.